HUBUNGAN LINGKUNGAN FISIK RUMAH DENGAN KEJADIAN PENYAKIT PNEUMONIA PADA BALITA DI WILAYAH KERJA PUSKESMAS PEKAYON JAYA KOTA BEKASI - Safira Fatichaturrachma; Suhartono Suhartono; Dharminto Dharminto (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2016)
Pneumonia is an acute infection of the lung tissue. Pneumonia in infants is a serious infection and affects many children around the world. In 2014 at West Java, the number of patients of pneumonia as much as 206.133 children under five years old. This study aums to determine physical condition of the home environment with the incidence of pneumonia in children under five years old in Puskesmas Pekayon Jaya Bekasi City.This research used observational analytic study with case control study design. Samples were obtained by 76 respondents. 38 respondents of case group and 38 respondents of control group. Analyzed using univariate and bivariate with Chi Square test. The result shown from 9 variables there are 5 variables which associated with the incidence of pneumonia in children under five are spacious of house ventilation (p-value=0.049; OR=3.923; 95%CI= 1.134 to 13.576), the moisture level of home (p-value=0.040; OR=3.478; 95%CI= 1.172 to 10.323), the presence smokers in home (p-value=0.039; OR=2.949; 95%CI= 1.159 to 7.503), home lightning conditions (p-value=0.035; OR=3.111; 95%CI= 1.188 to 8.147) and the condition of home temperature (p-value=0,021; OR=3.322; 95%CI= 1.293 to 8.538). It can be concluded that the physical environment of the home associated with pneumonia in children under five in Puskemas Pekayon Jaya Bekasi City is home ventilation, moisture level home, the presence of a smoker in the house, home lighthing conditions, and the house temperature conditions.